Bridging the gap between Higher education and self-employment: FPE economy department students’ perspectives on Digital entrepreneurship - Zakaria AAMOU; Souad BELHORMA (African Scientific Journal, 2025)
ABSTRACT Entrepreneurship represents a viable career alternative for university graduates. Accessing the Moroccan job market represents a real challenge, particularly due to elevated unemployment rates and the substantial number of graduates vying for limited work opportunities. In this unpredictable work context, entrepreneurship education instills in students the principles of self-employment, project management and leadership that can offer alternative work opportunities for university graduates. This study aims to assess the perceptions of Economy department students at the polydisciplinary faculty of Errachidia Morocco regarding entrepreneurship education and its potential contribution to their self-employment. To this end, a quantitative research design was adopted, deploying an online survey that was distributed to economy department students, N=300, to gauge their perceptions on how digital entrepreneurship education might connect them to the job market. Findings demonstrated that students hold positive perceptions vis-à-vis digital entrepreneurship education and believe that it can positively bridge the gap between higher education institutions and self-employability. Keywords Digital Entrepreneurship education, Digitalization, University graduates, Entrepreneurial intention.